Theorizing sustainability: How to better understand the social puzzle of alternative coordination forms - Maurer, Andrea (Zeitschrift für Theoretische Soziologie, 2026)
This article presents a research strategy that aims to develop sociological theories methodologically. This type of theorizing is applied to the issue of why sustainable use of limited natural resources is so difficult to achieve, even though it would be beneficial for the majority. While mainstream research currently focuses on markets versus government regulation, this article presents forms of social self-governance as alternatives and discusses their rise and functioning. The goal of developing expanded theories in this case is to provide explanations that clearly show why certain social factors, constellations, and mechanisms can contribute to the collective goal of a more sustainable future. Action-based explanations are an important tool for this type of theory formation, as they can be expanded with reference to methodological principles and give explanations for why specific social aspects are relevant. To this end, the article identifies and differentiates between two types of theorizing and shows in which ways they expand sociological theories and what explanations they offer for the social puzzle of the constant rise and fall of alternative coordination forms. The first approach strives for theories of the middle range based on context-related models and emphasises the interaction between individuals and social context. The second approach uses a general principle of action in order to capture the effects of social factors in light of individual properties. Both approaches support the construction of more realistic theses and contribute to the debate on theory formation in sociology, which in turn will enhance the analysis of how a more sustainable way of life can be organised by cooperative coordination forms.